(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The article details the concepts of comorbidity, analyzes the causes of the combined pathology and factors affecting its development and progression, and discusses options for classifying comorbidity. Much attention is paid to the structure of the final diagnosis and the rules of its formulation. The review characterizes the features of modern human pathology. It is devoted to comorbidity, or syntropy – diversity, or the coexistence of two or more diseases in one patient.